2022
DOI: 10.1186/s12883-022-02892-y
|View full text |Cite|
|
Sign up to set email alerts
|

Risk factors for aneurysm rupture among Kazakhs: findings from a national tertiary hospital

Abstract: Background Rupture of intracranial aneurysms (RIA) leads to subarachnoid hemorrhage (SAH) with severe consequences. Although risks for RIA are established, the results vary between ethnic groups and were never studied in Kazakhstan. This study aimed to establish the risk factors of RIA in the Kazakh population.  Methods Retrospective analysis of 762 patients with single IAs, who attended the neurosurgical center from 2008 until 2018, was conducted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Consequently, atherosclerosis may be the etiology of SAH in this patient ( 19 , 20 ). Furthermore, the patient had a history of hypertension and irregular control of blood pressure may be one of the factors for inducing aneurysm rupture ( 21 , 22 ). In the present case, acute paraplegia developed immediately after the onset of aneurysmal SAH and the possibility of hemorrhage causing spinal vasospasm was considered.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, atherosclerosis may be the etiology of SAH in this patient ( 19 , 20 ). Furthermore, the patient had a history of hypertension and irregular control of blood pressure may be one of the factors for inducing aneurysm rupture ( 21 , 22 ). In the present case, acute paraplegia developed immediately after the onset of aneurysmal SAH and the possibility of hemorrhage causing spinal vasospasm was considered.…”
Section: Discussionmentioning
confidence: 99%
“…Its high mortality and prevalence in cardiovascular diseases have garnered significant attention. In Central and Eastern European countries, the estimated incidence of CA among adults is 3.2% [4,5]. The multifaceted pathogenesis of cerebral aneurysms involves various factors, including genetic predisposition, hemodynamic stress, and environmental influences [6].…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported an error in the article title. The word “hospital” is missing.…”
mentioning
confidence: 99%